2018
DOI: 10.7224/1537-2073.2017-093
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip and Knee Arthroplasty in Patients with Multiple Sclerosis

Abstract: CME/CNE Information Activity Available Online: To access the article, post-test, and evaluation online, go to http://www.cmscscholar.org. Target Audience: The target audience for this activity is physicians, physician assistants, nursing professionals, and other health-care providers involved in the management of patients with multiple sclerosis (MS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The average postoperative pain, measured by the visual analogue scale, was significantly reduced compared to the preoperative situation (8.6 vs. 2.9). 70 % of patients would recommend the operation [16]. The modified Harris Hip Score indicated a significantly less favorable functional outcome in the MS cohort (average 66 vs. 80 points; p < 0.001).…”
Section: Patient Satisfaction and Functional Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The average postoperative pain, measured by the visual analogue scale, was significantly reduced compared to the preoperative situation (8.6 vs. 2.9). 70 % of patients would recommend the operation [16]. The modified Harris Hip Score indicated a significantly less favorable functional outcome in the MS cohort (average 66 vs. 80 points; p < 0.001).…”
Section: Patient Satisfaction and Functional Resultsmentioning
confidence: 92%
“…Existing studies on hip arthroplasty in multiple sclerosis. Newman et al 2017 [5] US database analysis (NIS) 5899 MS vs. 2 723 652 non-MS patients Rondon et al 2018 [15] Retrospective cohort study with control group 76 MS vs. 187 non-MS patients (62 THAs and 46 TKAs) Total hip arthroplasty, TKA = Total knee arthroplastymid-term revision rate of 13% was observed in an smaller retrospective study with 30 MS patients[16]. Lower revision rates of 7.3 % were found in the work of Newman et al, where the THA survival rate after 8 years was also 91.5 %[14].…”
mentioning
confidence: 99%
“…MS patients demonstrated lower modified Harris Hip Score and Hip Disability and Osteoarthritis Outcome Score Joint Replacement hip function scores than control despite receiving increased physiotherapy care although this may be partly reflective of progression of their disease during the period of this study as demonstrated by worsening of mMSIS scores. Results from the included MS THA studies are displayed in [ 53 ] Figure 4 .
Figure 4 Total hip arthroplasty in multiple sclerosis results.
…”
Section: Resultsmentioning
confidence: 99%
“…22 Our findings corroborate the literature in regards to the increased risk of UTI. 14,15,17,23 Almost 96% of patients with MS have bladder dysfunction, which predisposes patients to UTI. 24 This fact along with the high prevalence of use of steroids and other immunologic therapies can exacerbate their risk for infections.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several orthopedic studies analyzing postoperative complications of patients with neuromuscular conditions undergoing total hip arthroplasty 12,14–17. These studies demonstrated that patients with MS are at increased risk for postoperative complications, postoperative infections, and other medical complications.…”
mentioning
confidence: 99%